Association Between Serum Magnesium Levels and Blood Pressure in Diabetic Patients. A Comparative Study - Zahid Habib Qureshi, Abida Jaffar, Ali Hamza Malik, Fatima Faiz, Bakhtawar Farooq, Ejaz Hussain Sahu (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Magnesium is a vital intracellular cation that regulates vascular tone, insulin sensitivity, and enzymatic activity. Hypomagnesemia has been reported frequently in patients with type 2 diabetes mellitus, and it may play a role in the pathogenesis of hypertension. However, limited data are available from South Asian populations. Objective: This study aimed to assess serum magnesium levels in diabetic patients, compare them with healthy controls, and determine their association with blood pressure. Methods: A comparative cross-sectional study was conducted at Multan Medical and Dental College (MMDC) and Nishtar Medical University, Multan, from May 2022 to June 2023. A total of 140 participants were enrolled, including 70 patients with type 2 diabetes mellitus and 70 age- and sex-matched healthy controls. Demographic and clinical data were recorded. Blood pressure was measured using a standardized sphygmomanometer protocol. Fasting venous blood samples were collected, and serum magnesium was estimated using the colorimetric xylidyl blue method. Data were analyzed with SPSS v26 using independent t-tests and Pearson’s correlation. A p value <0.05 was considered statistically significant. Results: Serum magnesium was significantly lower in diabetic patients (1.65 ± 0.23 mg/dL) compared to controls (1.91 ± 0.21 mg/dL, p < 0.001). Diabetic patients also exhibited higher systolic blood pressure (143.2 ± 12.1 vs. 126.4 ± 9.5 mmHg, p < 0.001) and diastolic blood pressure (89.4 ± 7.1 vs. 78.6 ± 6.4 mmHg, p < 0.001). A significant negative correlation was observed between serum magnesium and both systolic (r = –0.41, p < 0.01) and diastolic blood pressure (r = –0.38, p < 0.01) in diabetics. Conclusion: Hypomagnesemia is common among diabetic patients and is significantly associated with higher blood pressure. Regular monitoring and timely correction of magnesium deficiency may contribute to improved blood pressure control and reduction of cardiovascular risk in this population. Keywords: Serum magnesium, hypertension, diabetes mellitus, hypomagnesemia, blood pressure